A docking-based structural analysis of geldanamycin-derived inhibitor binding to human or Leishmania Hsp90 - Palma, Luana Carneiro (2019)
Conselho Nacional de Pesquisa e Desenvolvimento Científico (P.S.T.V. – Universal 422867/2016-0 http://www.cnpq.br) and Fundação de Amparo a Ciência e Tecnologia do Estado de Pernambuco (LFGRF – BFP-0063-4.03/17). P.S.T.V. holds a grant from CNPq for productivity in research (307832/2015-5).